Posterior reversible encephalopathy syndrome a rare presentation of post?streptococcal glomerulonephritis - Dudipala, Sai Chandar; Prashanthi, M; Kumar Ch, Laxman (Indian Journal of Child Health, 2020)
Acute post-streptococcal glomerulonephritis (PSGN) is a classic example of acute nephritic syndrome in children. It is typically characterized by gross hematuria, edema, hypertension, and acute kidney injury (AKI). Patients show diverse clinical profiles from being asymptomatic to mild syndrome or significant complications such as AKI, cardiac failure, or encephalopathy. Hypertension is found in up to 90% of patients and only 10% may have neurological symptoms. Only a few present with posterior reversible encephalopathy syndrome (PRES). Although PRES is a rare, but severe complication, there is a good outcome with appropriate treatment. Here, we report a case of PSGN in an 11-year-old female child who presented with altered sensorium, seizures, and vision loss. She was diagnosed as PRES on neuroimaging, which recovered with appropriate treatment.